Cobalt protoporphyrin modulates antioxidant enzyme activity in the hypothalamus and motor cortex of female rats: CoPP effect on antioxidant enzymes in rat brain - Serrano-García, Norma; Pinete-Sánchez, Raúl; Medina-Campos, Omar Noel; Ramos-Santander, Minerva Adriana; Pedraza-Chaverri, José; Orozco-Ibarra, Marisol (Cellular and Molecular Biology, 2024)
Cobalt protoporphyrin (CoPP) is a synthetic heme analog that has been observed to reduce food intake and promote sustained weight loss. While the precise mechanisms responsible for these effects remain elusive, earlier research has hinted at the potential involvement of nitric oxide synthase in the hypothalamus. This study aimed to delve into CoPP’s impact on the activities of crucial antioxidant enzymes: superoxide dismutase (SOD), catalase, glutathione peroxidase (GPx), glutathione reductase (GR), and glutathione-S-transferase (GST) across seven distinct brain regions (hippocampus, hypothalamus, prefrontal cortex, motor cortex, striatum, midbrain, and cerebellum), as well as in the liver and kidneys. Female Wistar rats weighing 180 to 200 grams received a single subcutaneous dose of 25 μmol/kg CoPP. After six days, brain tissue was extracted to assess the activities of antioxidant enzymes and quantify malondialdehyde levels. Our findings confirm that CoPP administration triggers the characteristic effects of decreased food intake and reduced body weight. Moreover, it led to an increase in SOD activity in the hypothalamus, a pivotal brain region associated with food intake regulation. Notably, CoPP-treated rats exhibited elevated enzymatic activity of catalase, GR, and GST in the motor cortex without concurrent signs of heightened oxidative stress. These results underscore a strong connection between the antioxidant system and food intake regulation. They also emphasize the need for further investigation into the roles of antioxidant enzymes in modulating food intake and the ensuing weight loss, using CoPP as a valuable research tool.